Roseicella aerolata GB24T from bioaerosol attenuates Streptococcus pneumoniae-introduced inflammation through regulation of gut microbiota and acetic acid - Qin, Tian; Yu, Ting; Liu, Yuqi; Wu, Jiguo; Jiang, Yunxia; Zhang, Guoxia (Frontiers in Microbiology, 2023)
Streptococcus pneumoniae (Spn) is the most common respiratory pathogen causing community-acquired pneumonia. Probiotics represent a new intervention target for Spn infection. Hence, the discovery and development of new potential probiotic strains are urgently needed. This study was designed to investigate the beneficial effect and mechanism of a new bacterium named Roseicella aerolata GB24T that antagonizes Spn at cellular and animal levels. The results revealed that GB24T strain inhibited the growth of Spn on sheep blood agar plates, forming inhibition circles with a diameter of 20 mm. In cultured bronchial epithelium transformed with Ad 12-SV40 2B (BEAS-2B) cells, Spn infection induced an elevation in the expression levels of interleukin-1β, interleukin-6, and tumor necrosis factor-α to 4.289 ± 0.709, 5.587 ± 2.670, and 5.212 ± 0.772 folds compared to healthy controls, respectively. Moreover, pre-infection with GB24T for 1.5 h almost eliminated the cellular inflammation caused by Spn infection. Additionally, male Sprague–Dawley rats infected with Spn were randomly allocated into two groups: GB24T pre-infection and Spn infection groups, with healthy rats as control. GB24T significantly alleviated inflammatory lung injury caused by Spn infection, which was associated with obvious changes in the abundance of gut microbiota and a trend toward enhanced secretion of short-chain fatty acids, especially acetic acid. Acetic acid was validated to be effective in alleviating inflammation due to Spn infection in cellular assays. Together, these findings highlight that GB24T strain is an important protective feature in the respiratory tract.